2013
DOI: 10.1111/pala.12034
|View full text |Cite
|
Sign up to set email alerts
|

Microbes, mud and methane: cause and consequence of recurrent Early Jurassic anoxia following the end‐Triassic mass extinction

Abstract: The end-Triassic mass extinction (c. 201.6 Ma) was one of the five largest mass-extinction events in the history of animal life. It was also associated with a dramatic, long-lasting change in sedimentation style along the margins of the Tethys Ocean, from generally organic-matter-poor sediments during the Triassic to generally organic-matterrich black shales during the Jurassic. New core material from Germany provides biomarker evidence of persistent photiczone euxinia during the Hettangian, the onset of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 176 publications
1
68
0
Order By: Relevance
“…Severe environmental changes have also been reported in the same interval, notably a meteorite impact (Olsen et al 2002;Smit et al 2014) and flood volcanism (Schoene et al 2010;Whiteside et al 2010). However, precise stratigraphic correlation in between all these biotic events and between the biotic and abiotic events is still wanting (see reviews of Hesselbo et al 2002;Deenen et al 2010;Van de Schootbrugge et al 2013). On the other hand, close analyses reveal that many groups, especially among invertebrates and microvertebrates, have a rather diffuse, non-catastrophic Late Triassic turnover characterized by elevated extinction rates during the entire NorianRhaetian interval (Cuny 1995;Tanner et al 2004;Bambach 2006;Mander et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Severe environmental changes have also been reported in the same interval, notably a meteorite impact (Olsen et al 2002;Smit et al 2014) and flood volcanism (Schoene et al 2010;Whiteside et al 2010). However, precise stratigraphic correlation in between all these biotic events and between the biotic and abiotic events is still wanting (see reviews of Hesselbo et al 2002;Deenen et al 2010;Van de Schootbrugge et al 2013). On the other hand, close analyses reveal that many groups, especially among invertebrates and microvertebrates, have a rather diffuse, non-catastrophic Late Triassic turnover characterized by elevated extinction rates during the entire NorianRhaetian interval (Cuny 1995;Tanner et al 2004;Bambach 2006;Mander et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2) indices, indicate reduced bottom-water oxygen across the duration of ecological stress estimated as ~600 k.y. based on correlation to the Newark Basin presented in Whiteside et al (2010) and into the Early Jurassic relative to Late Triassic background values, with a temporary return to oxic conditions immediately after the ETE, as observed elsewhere (e.g., van de Schootbrugge et al, 2013;Richoz et al, 2012). Notably, biomarker concentrations indicative of PZE became established following the development of reducing conditions in bottom waters (e, d in Fig.…”
Section: A 3 My Record Of Environmental and Ecological Changementioning
confidence: 99%
“…Carbon cycle anomalies and recurrent anoxia persisted throughout much of the Hettangian (Bartolini et al 2012), and further anoxic and dysoxic episodes are reported from the Sinemurian and Pliensbachian (van de Schootbrugge et al 2013). Finally, the Pliensbachian-Toarcian Anoxic Event is well known as the most likely cause of the end-Pliensbachian extinction event.…”
Section: Discussionmentioning
confidence: 99%
“…During and after the end-Triassic biotic crisis, anoxic or dysoxic bottom waters were wide-spread, likely related to changing oceanographic patterns due to the breakup of Pangaea and the opening of the Atlantic Ocean (Hallam 1981, Hallam & Wignall 1997, van de Schootbrugge et al 2013. Carbon cycle anomalies and recurrent anoxia persisted throughout much of the Hettangian (Bartolini et al 2012), and further anoxic and dysoxic episodes are reported from the Sinemurian and Pliensbachian (van de Schootbrugge et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation